Characterisation of New Rat Cytomegalovirus Isolates from Rice-Field Rats (Rattus Argentiventer) - Lai , Kit Yee (1999)

(untitled)
A serological survey for virus infections in rice field rats, Rattus argeniventer was conducted in five different geographic locations of Malaysia to identify viruses that have potential use in biological control of rat populations. The results indicated that rat cytomegalovirus (RCMV) was most prevalent, 50% of the rats had serum antibody to RCMV. Rat coronavirus was fairly common (16%) in these places, while relatively few «5%) animals had antibodies against mouse adenoviruses, rat parvoviruses, Theiler's virus and Reovirus. None of the rat populations were found to have lymphocytic choriomeningitis virus, vaccinia virus, Hantaan virus, Seoul virus, pneumonia virus and Sendai virus implied that the local rice field rats were free from viruses that cause zoonotic diseases in human and livestock. Based on the present data, only RCMV fulfil the essential requirement to become an ideal virus for fertility control in rats since this virus has infected most of the population without causing lethal disease. Rat cytomegaloviruses were successfully isolated from the kidneys and salivary glands of seropositive animals. The isolates had common herpesvirus morphology and produced typical cytomegalo-like cytopathic effects in rat embryonic fibroblasts that were comparable with those of the English strain of RCMV. Ultrastructural examination of the infected cells revealed two types of virus nucleocapsids: empty capsids and capsids with electron-dense core. Infected cells were characterised by chromatin margination, the presence of tubular structures and the formation of dense bodies. The cytopathogenicity of these viral agents was investigated by using indirect immunoperoxidase and indirect immunofluorescence assays. Staining of the English RCMV and the local isolates by both homologous and heterologous antisera indicated that these three RCMV isolates were antigenically similar. Both the isolates were host specific and relatively slow growing. Since morphological and (cyto )pathological aspects failed to distinguish the two Malaysian isolates and the English RCMV, protein profiles of these viruses were compared. Protein compositions of extracellular virions were analysed by SDSPAGE. Present finding showed that protein compositions among the RCMV isolates were slightly different in the ratios. Based on antigenic variation that exists among strains, Western blot successfully demonstrated that the three isolates were distinct from one another. In conclusion, the study showed that RCMV is a suitable vector to carry immunocontraceptive gene because this virus has naturally infected the rats. The release of RCMV based contraceptive vaccine therefore would not introduce a new virus to the environment. Persistent and latent infection establishes by RCMV could ensure long-lasting immune response. RCMV infection is species specific. It failed to replicate in non-rat cells thereby keeping other native species at low risk.